The Bodily Incorporation of Mechanical Devices: Ethical and Religious Issues (Part 1) - Campbell, Courtney S. (Cambridge quarterly of healthcare ethics, 2007)
A substantial portion of the developed world's population is increasingly dependent on machines to make their way in the everyday world. For certain privileged groups, computers, cell phones, PDAs, Blackberries, and IPODs, all permitting the faster processing of information, are commonplace. In these populations, even exercise can be automated as persons try to achieve good physical fitness by riding stationary bikes, running on treadmills, and working out on cross-trainers that send information about performance and heart rate.This essay is drawn from collaborative research conducted under the auspices of the “Altering Nature: How Religious Traditions Assess the New Biotechnologies” project at Rice University from 2002 to 2004 through the financial support of The Ford Foundation (Grant #1010-1601). The paper is submitted with the permission and acknowledgement of the project coordinators and The Ford Foundation. The authors also acknowledge the research and editorial assistance of Dr. Siobhan Baggot and Ms. Sarah Gehrke.